Molecular Docking of Physalis angulata and Schleichera oleosa as a Potential Inhibitor of Dengue methyltransferase - Hasan, Rahmawaty; Lady Yunita Handoyo, Diana; Zukhruf, Laila (Al-Kimia, 2023)
Indonesia as the 2nd country with the largest Dengue Hemorrhagic Fever (DHF) cases among 30 countries with endemic areas. Oral infusion of Physalis angulata and Schleichera oleosa are potential plants that is traditionally applied for DHF treatment. This study aimed to analyze the chemical compounds of Physalis angulata and Schleichera oleosa as an alternative therapy to DHF utilizing the molecular docking procedure. The methods are macromolecule and ligand preparation, validation as well as molecular docking, data analysis and visualization. The compounds were downloaded from the PubChem database and dengue methyltransferase protein was obtained from PDB (1L9K). Molecular docking has interacted with the Autodock and analyzed by Pymol, Discovery Studio Visualizer and Ligplot. The results revealed that the test ligands had lower binding energies than the SAH as a native ligand, specifically 14-Hydroxyixocarpanolide -10.69 kcal/mol as a potential compound from Physalis angulata and Schleicherastatin 5 -10.25 kcal/mol as a potential compound from Schleichera oleosa. With hydrogen bonds and hydrophobic pockets, all of the test ligands bind the NS5 dengue methyltransferase active site. The results suggested that Physalis angulata and Schleichera oleosa possess offering compounds for inhibiting NS5 dengue methyltransferase as a DHF treatment.